Effect of Bismuth Precursor and Temperature on Properties of Bismuth Vanadate Photocatalyst - Abdullah, A.H.; Jong, C.Y.; Irmawati, R. (Asian Journal of Chemistry, 2011)
Bismuth vanadate (BiVO4) photocatalysts were synthesized via solution combustion method using two different bismuth precursors (bismuth nitrate and bismuth acetate), ammonium metavanadate and citric acid as a reducing agent/fuel. The BiVO4 samples formed were spherical but highly agglomerated with monoclinic scheelite structure. Photocatalytic activities of synthesized BiVO4 were evaluated by photodegrading methylene blue dye under visible light irradiation. Although BiVO4 synthesized prepared using bismuth nitrate and combusted at 600 ºC has the lowest surface area, it exhibited the highest photocatalytic activity due to its high monoclinic scheelite structure. It shows that the crystallinity of BiVO4 is more important than surface area in photodegradation of methylene blue.